Changes in yield and quality of melon dried fruit grown using different types of fertilization (Texas Journal of Agriculture and Biological Sciences, 2022)
According to the data, more than 30-35% of the fruit and vegetable crops are dying due to various reasons. The main causes of wastage are high weather temperature during the harvesting period, not picking the product at the right time according to the degree of ripeness, and not conducting the post-harvest activities properly, etc